2022
DOI: 10.1039/d2ob00590e
|View full text |Cite
|
Sign up to set email alerts
|

d-Allose, a rare sugar. Synthesis of d-allopyranosyl acceptors from glucose, and their regioselectivity in glycosidation reactions

Abstract: Although D-allose (D-All) is a sugar with low natural abundance, it has a great pharmacological and alimentary potential due to its biological properties. However, its chemistry, regarding the regioselectivity in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Traditionally, these reactions are either performed on suitably protected monosaccharides (for an overview of the methods to synthesize allose using protecting groups, see a recent review) 8 or enzymatically. The use of enzymes in these epimerization reactions mostly requires the unprotected reducing sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, these reactions are either performed on suitably protected monosaccharides (for an overview of the methods to synthesize allose using protecting groups, see a recent review) 8 or enzymatically. The use of enzymes in these epimerization reactions mostly requires the unprotected reducing sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Rare sugars are saccharides that exist in small quantities in nature and have attracted attention for their functions such as their ability to suppress postprandial blood glucose elevation [1,2]. Recently, enzymatic syntheses of monosaccharide rare sugars such as psicose and allose have been established [3][4][5], enabling their mass production and availability; it has also been reported that several rare sugars can be chemically synthesized via siteselective epimerization [6,7]. With this progress, novel oligosaccharides and glycosides derived from these monosaccharides and rare sugars by chemical synthesis could result in the creation of new functional food products.…”
Section: Introductionmentioning
confidence: 99%
“…In general, an efficient enzymatic synthesis based on the Izumoring strategy has high specificity, which makes it environmentally friendly and sustainable, making it a highly favorable alternative to chemical synthesis for the preparation of d -allose. l -Rhamnose isomerase (L-RI), which is responsible for the isomerization of d -allulose to d -allose, is the preferred biocatalyst for the synthesis of d -allose. Several L-RIs have been identified and substantially investigated, but the studies largely concentrated on gene mining, strain screening, and enzymatic characterization . In all cases, the broader commercialization of these enzymes has been restricted by poor operational stability under harsh industrial reaction conditions.…”
Section: Introductionmentioning
confidence: 99%